BRUNEI DARUSSALAM'S E-GOVERNMENT STRATEGY IN OVERCOMING CYBER THREATS - Mahendro Bhirowo; Fauzia Gustarina Cempaka Timur; Mardi Siswoyo (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2018)
E-Government is a government administration system that plays a vital role in the international global communication, and greatly determines the progress of a state. However, the government administration system that utilizes Information and Communication Technology may be exposed to threats, especially threats originating from cyberspace. This research was carried out with the aim to analyze Brunei Darussalam's E-Government strategy in overcoming cyber threats. This study uses descriptive qualitative research methods accompanied by data obtained from the presentations and interviews during the overseas field study visits in Brunei Darussalam by the representatives of the Ministry of Foreign Affairs and Trade (MOFAT), IT Protective Security Services (ITPSS), and the Prime Minister’s Office (PMO) of Brunei Darussalam, as part of a research related to Brunei Darussalam's e-Government strategy in overcoming cyber threats. The results of this study indicate that the Brunei Darussalam’s e-Government strategy in overcoming cyber threats was carried out by focusing on citizen-centric service delivery in stages. It begins with the establishment of a law on computer abuse in 2000, followed by the establishment of Brunei National Computer Emergency Response Team (BruCERT) in 2004, introduction of Internet Ethics and Cyber Security Awareness Program in 2009, and the development of a national cyber security framework in 2014. All are integrated into a common policy coined as Brunei Insight 2035. This can be an input for the implementation of e-Government in Indonesia, in order to improve the equality and openness of access to information and communication in Indonesia, without neglecting the principles of security and comfort in communicating and obtaining information.